PSYCHOLOGICAL ABILITY OF REFLECTIVE DISCOURSE IN PSYCHOTHERAPY OF LATENT DESTRUCTIVE CONTENTS OF PERSONAL PSYCHE (Psychology Travelogs, 2024)
The article highlights the problem of the psychological uniqueness of the hidden destructive tendencies of the individual, in particular, the tendency to commit suicide. It is noted that the lack of theoretical substantiation of productive methods of suicide prevention and personality rehabilitation, taking into account unique personal characteristics that determine suicidal tendencies, determines the relevance of scientific and psychological intelligence.Suicide is considered as an act of suicide, which is carried out in a state of severe mental disorder or under the influence of a mental illness; a conscious act of self-removal from life under the influence of acute psycho-traumatic situations, in which one's own life as a higher value loses its meaning. In the conditions of unbearable life or insurmountable obstacles, hidden suicide most often takes place - a behavior characteristic of suicidal persons that indirectly leads them to death, in particular, by destroying their own health.A characteristic feature of the mental life and behavior of a person with suicidal tendencies is narrowing of consciousness. The specificity of behavior testifies to the rigidity of the strategy and structure of his life activities. It is noted that, taking into account the specifics of the individual's mental state, reflective practices show high productivity in the psychotherapeutic process of suicidal tendencies.A highly capable psychotherapeutic means of rehabilitating latent destructive tendencies of the individual is substantiated by reflective discourse. The potential properties of reflective discourse: openness, non-linear nature, dynamic integrity, unpredictability of the course, transgressiveness, combined with the functions of reflection to ensure complex processes of self-knowledge, decoding of latent contents, their transformation, correspond to the features of psychological rehabilitation and constructive personality development.
Keywords: personality; psychological rehabilitation; psychological health; reflection; reflective discourse; suicide; latent tendencies; destructive tendencies